OPTIMIZING THE TOURISM SECTOR IN SANGGAU TO INCREASE ITS LOCAL REVENUE - B2053151001, TOMI (Jurnal Ekonomi Daerah (JEDA), 2017)
Regional autonomy has given authority to local regions and districts to be more independent in managing and organizing local government, including the use of resource that could potentially create economic growth from the tourism sector. Utilization of the tourism sector became one of the efforts to increase local revenue (PAD) for financing regional development. Effective management of the tourism sector that can stimulate regional economic growth in the form of revenue expenditure of tourists visiting the area by incrising retribution from the area. It can also boost earnings in other sectors such as incomes from hotel tax, restaurant tax and entertainment tax. This research aimed to estimate the magnitude of the potential annual incomes of Sanggau from the tourism sector. The research also examined the effect of budget realization of tourism to the number of visitor attractions, the hotel tax revenue, restaurants tax revenues and the entertainment taxes revenues. Then the influence of the number of visitor attractions to acceptance of retribution, the influence of the number of visitor attractions of the hotel tax revenue, the effect of the number of visitor attractions to restaurants tax revenues, and the influence of the number of visitors to incomes from entertainment taxes in Sanggau. Based on the results of the research it can be concluded that if the twenty one attractions that have been classified have 156,399 visitors, Sanggau government could receive additional retribution of at least Rp. 781,995,000, - and maximum of Rp. 1,563,990,000, -. The findings also showed that the realization of budget from tourism significantly influenced the number of visitors, hotel and restaurants taxes, but did not significantly affect the revenues from entertainment taxes. The number of visitors then significantly affected the acceptance of tourism retribution. However, the number of tourism visitors did not significantly affect the revenues from hotel, restaurants and entertainment taxes in Sanggau. Keywords : The tourism sector, tourism budget, tourism visitor, tourism retribution, hotel tax, restaurant tax, entertainment tax, district revenue.